Analisis Sistem Informasi Akuntansi Pengeluaran Kas pada CV Macarindo Berkah Group Jember - Tiara Tiara; Fitri Ayu Winarni; Sri Kantun (Ekuitas: Jurnal Pendidikan Ekonomi, 2021)
This study analyses the Accounting Information System (AIS) of CV Macarindo Berkah Group Jember’s Cash Expenditures. Data collection was carried out by document and interview methods. The data analysis method used is descriptive evaluative. The results showed that the AIS cash disbursements of CV Macarindo Berkah Group Jember were by the applicable AIS standards with a suitability level of 79%. The suitability consists of AIS components of cash disbursements, documents, accounting records, functions, and document flowcharts. So it can be concluded that it follows the applicable AIS standards, but not maximally due to several shortcomings, including the absence of activity to approve supplier invoices, no petty cash disbursement journal, and no cash fund holder function. Based on the results obtained, the authors submit suggestions to CV Macarindo Berkah Group Jember to continue to improve the AIS cash disbursement by studying AIS standards and recruiting employees who better understand the AIS cash disbursements.